The amino-terminal one-third of the influenza virus PA protein is responsible for the induction of proteolysis. - Sanz-Ezquerro, J J (1996)
We have previously described the fact that the individual expression of influenza virus PA protein induced a generalized proteolysis (J.J. Sanz-Ezquerro, S. de la Luna, Ortin, and A. Nieto, J. Virol. 69:2420-2426, 1995). In this study, we have further characterized this effect by mapping the regions of PA protein required and have found by deletion analysis that the first 247 amino acids are sufficient to bring about this activity. PA mutants that were able to decrease the accumulation levels of coexpressed proteins also presented lower steady-state levels due to a reduction in their half-lives. Furthermore, the PA wild type produced a decrease in the stationary levels of different PA versions, indicating that is itself a target for its induced proteolytic process. All of the PA proteins that induced proteolysis presented nuclear localization, being the sequences responsible for nuclear transport located inside the first 247 amino acids of the molecule. To distinguish between the regions involved in nuclear localization and those involved in induction of proteolysis, we fused the nuclear localization signal of the simian virus 40 T antigen to the carboxy terminus of the cytosolic versions of PA. None of the cytosolic PA versions affected in the first 247-amino-acid part of PA, which were now located in the nucleus, were able to induce proteolysis, suggesting that conservation of a particular conformation in this region of the molecule is required for the effect observed. The fact that all of the PA proteins able to induce proteolysis presented nuclear localization, together with the observation that this activity is shared by influenza virus PA proteins from two different type A viruses, suggests a physiological role for this PA protein activity in viral infection.